Socioeconomic census of the disciplines of the administration course of a public university in the city of Sousa- PB (Research, Society and Development, 2019)
The objective of the present article is to present the result of an investigation about aspects of the social, cultural and academic reality of the students of the Administration Course of the Center of Juridical and Social Sciences of the Federal University of Campina Grande, Sousa, Paraíba and in this way to draw the profile socioeconomic level of those students. The methodology used for this work was based on descriptive and exploratory research. The research universe was all students actively enrolled in the Course. It was concluded that most of the universe is male, is between 16 and 27 years old, is considered white and brown, single, lives at home or apartment, still resides with family, studied fully in public school. It has as income, less than 1 to 2 minimum salaries, performs a function in the private sector, in the area of commerce. Among the issues of most interest to the students, issues related to public services and the country's economic situation, stood out.